Cancer stem cells in osteosarcoma. (1st February 2017) - Brown, Hannah K.; Tellez-Gabriel, Marta; Heymann, Dominique
Abstract: Osteosarcoma is the most common primary bone tumour in children and adolescents and advanced osteosarcoma patients with evidence of metastasis share a poor prognosis. Osteosarcoma frequently gains resistance to standard therapies highlighting the need for improved treatment regimens and identification of novel therapeutic targets. Cancer stem cells (CSC) represent a sub-type of tumour cells attributed to critical steps in cancer including tumour propagation, therapy resistance, recurrence and in some cases metastasis. Recent published work demonstrates evidence of cancer stem cell phenotypes in osteosarcoma with links to drug resistance and tumorigenesis. In this review we will discuss the commonly used isolation techniques for cancer stem cells in osteosarcoma as well as the identified biochemical and molecular markers. Highlights: Evidence of cancer stem-like cells in osteosarcoma. Involvement of cancer stem-like cells in drug resistance. Cancer stem-like cells as a source of therapeutic targets.